Research on Coverage Width Calculation and Analysis Based on Multibeam Bathymetric Model - Zhang, Junmeng (Transactions on Computer Science and Intelligent Systems Research, 2024)
As multibeam bathymetry is widely applied to the detection of complex terrain on the seafloor, how to optimize the coverage width and overlap rate by reasonably setting the measurement parameters has become a key issue in improving the accuracy and efficiency of the measurement. Starting from the actual situation, this study establishes a spatial geometric model based on the seabed topography. It combines the MATLAB programming tool to accurately calculate and analyze the coverage width of multibeam bathymetry and the overlap rate between neighboring strips under different circumstances. For example, when the opening angle of the multibeam transducer is 120 , the slope is 1.5 . The depth of seawater at the center point of the sea area is 70m, the model can calculate that when the distance of the measuring line from the center point is 200m, the coverage width is 224.81m and the overlap rate is 11.1%. On this basis, the influence of the position of the survey ship and the angle of the measuring line on the coverage width is discussed. For example, if the angle of the measuring line direction is 45 and the distance of the survey ship from the center of the sea is 0.3m, the coverage width of the beam is 451.79m. Through the calculation and analysis of the model, the working principle of the multibeam detector is accurately and concretely demonstrated to portray and describe the complex seabed terrain.